THE PRINCIPALSHIP IN THE TWENTY-FIRST CENTURY - Akinbode, Akintola Ismaila; Shuhumi, Said Rashid Ali (PUPIL: International Journal of Teaching, Education and Learning, 2018)
The success of every organization or institution relies heavily on the skillfulness of the leaders and managers anchoring the administration of such entity. Leadership is quite a herculean task which requires special trainings and updated skills in order to effectively govern both human and non-human resources of the institution. The school system, especially secondary schools, in the twenty-first century is quite different from the past centuries. Trends such as technology explosion, globalization, demographic changes, rising enrolment, knowledge-based economy, pressure for accountability coupled with call for value-based learning and financial constraints necessitate diversification of management strategies from the principals to administrators in order to achieve the stated goals and objectives of the school. The school is not an end in itself and purposely established to serve the society, principals have to brace up to acquire new strategies, and update their skills so that the schools will cope with the need of the contemporary society. For this reason, the principals have to be informed and updated on what they need to do in the school as the ‘father’ of the house. This paper, therefore, tries to reposition school leaders’ role from traditional notion to a more holistic and innovative conception in order to enhance the stratagem of both practicing and aspiring principals.